STRATEGI MANAJEMEN IMPRESI GIBRAN RAKABUMING DI INSTAGRAM MENJELANG PEMILIHAN WALI KOTA SOLO TAHUN 2020 - Nino Leonita, Gusti Ayu; Purnawan, Ni Luh Ramaswati; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2021)
2020 is synonymous with the political year, one of the regions that holds regional head elections is Solo. One of the candidate pairs in the Pilwalkot Solo is Gibran Rakabuming who’s promoted by PDIP. Gibran is actively campaigning on Instagram and it's considered an impression management practice. Impression management is a self-representation to JURNAL NIN control image when interacting with people. The quantitative descriptive content analysis method with the theory of 5 Impression Management Tactics by Jones and Pittman was used to analyze posts during the campaign period on @gibran_rakabuming Instagram account. Based on the analysis, the tactic most often used is ingratiation with sub indicators expressing sympathy for other parties 28 times and the least amount of tactics is intimidation with sub indicators expressing feelings of anger about something. This illustrates that Gibran only wants to highlight a positive image because it's considered to represent an ideal attitude of a leader.   Keywords: Content Analysis, Impression Management, Political PR, Instagram